The impact of cycle proficiency training on cycle-related behaviours and accidents in adolescence: findings from ALSPAC, a UK longitudinal cohort - Alison Teyhan; Rosie Cornish; Andy Boyd; Mary Sissons Joshi; John Macleod (BMC, 2016)
Abstract Background Cycle accidents are a common cause of physical injury in children and adolescents. Education is one strategy to reduce cycle-related injuries. In the UK, some children undertake National Cycle Proficiency Scheme [NCPS] training (now known as Bikeability) in their final years of primary school. It aims to promote cycling and safe cycling behaviours but there has been little scientific evaluation of its effectiveness. Methods The sample (n = 5415) were participants in the Avon Longitudinal Study of Parents and Children who reported whether or not they had received NCPS training. Outcomes were self-reported at 14 and 16 years: cycling to school, ownership of cycle helmet, use of cycle helmet and high-visibility clothing on last cycle, and involvement in a cycle accident. An additional outcome, hospital admittance due to a cycle accident from 11 to 16 years, was also included for a subsample (n = 2222) who have been linked to Hospital Episode Statistics (HES) data. Results Approximately 40 % of the sample had received NCPS training. Trained children were more likely to cycle to school and to own a cycle helmet at both 14 and 16 years, to have worn a helmet on their last cycle at age 14, and to have worn high-visibility clothing at age 16, than those who had not attended a course. NCPS training was not associated with self-reported involvement in a cycle accident, and only six of those with HES data had been admitted to hospital due to a cycle accident. Irrespective of training, results indicate very low use of high-visibility clothing, very few girls cycling as part of their school commute, and less than half of helmet owners wearing one on their last cycle. Conclusions Our results suggest cycle training courses for children can have benefits that persist into adolescence. However, the low use of cycle helmets, very low use of high-visibility clothing, and low levels of cycling to school for girls, indicate the further potential for interventions to encourage cycling, and safe cycling behaviours, in young people.